Necrotizing Autoimmune Myopathy: A Rare Variant of Idiopathic Inflammatory Myopathies - Noman Ahmed Jang Khan MD; Shaza Khalid MD; Saad Ullah MD; Muhammad Umair Malik MD; Samer Makhoul MD (SAGE Publishing, 2017)
Idiopathic inflammatory myopathies are an unusual group of myopathies with annual incidence of 1 in 100 000 people in the United States. Necrotizing autoimmune myopathy comprises only 16% of this group. It usually presents with severe proximal weakness, lower extremity weakness, and severe fatigue while very rarely does it present with dysphagia and respiratory muscle weakness. Statin use, cancer, and connective tissue disorder are the usual associated risk factors. Anti-signal recognition particle and 3-hydroxy-3-methylglutaryl-coenzyme A reductase are the 2 most common autoantibodies associated with necrotizing autoimmune myopathy. In this article, we present a very rare case of a 66-year-old male who presented with shortness of breath and dysphagia requiring intubation and ventilator support. Creatine kinase was 23 000, myoglobin was 7000, and ANA was positive. All other autoimmune and infectious workup including Lyme disease was unremarkable. Muscle biopsy turned out remarkable for necrotizing myopathy. No evidence of statin use, active malignancy, or connective tissue disease was found. He was treated with high-dose corticosteroids and a short course of intravenous immunoglobulin with very mild improvement in symptoms. Anti-signal recognition particle and 3-hydroxy-3-methylglutaryl-coenzyme A reductase could not be performed as the patient refused to pursue further medical testing. This is a very rare case of idiopathic inflammatory myopathy presenting with bulbar and respiratory muscle weakness requiring ventilator support.